Sistem Informasi Pendataan Pasien Jamkesda Pada Puskesmas Aras Kabu Kecamatan Beringin - Benny Saputra (Journal of Information System Research (JOSH), 2019)
Information on the data collection of JamKesDa Aras Kabu patients that has been done using Ms.word, even then it is only the creation of the copy, while for the data input is still done by writing in a book, thus causing considerable time to obtain the desired information and also less effective in archival storage. The problem faced in handling patient information systems is the length of data collection because it still uses a system that is not adequate. Therefore the author tries to design a new system that is expected to help in reducing existing problems so far. In this study the authors used a computerization of the Kabu Aras Health Center by using the Visual Basic 2008 programming language as an interface, Mysql for the database and and Crystal Report for reporting and are expected to be an alternative for adjusting the data collection problems of JamKesDa patients in the Aras PusKesMas Aras Kabu.